Marketing budgeting in the upper echelons - JIANG, Junqiu (Institutional Knowledge at Singapore Management University, 2024)
Marketing professionals and academics frequently highlight the challenges of obtaining and protecting the marketing budget. However, prior academic research predominantly focusses on the optimal allocation of a given marketing budget, with little attention directed towards understanding the organizational process of securing approval for the marketing budget. Accordingly, this dissertation addresses this gap with two essays examining the marketing budgeting process by drawing on the theories-in-use (TIU) of both Chief Marketing Officers (CMOs) seeking approval for the marketing budget, and Chief Executive Officers (CEOs) approving the marketing budget. In Essay 1, I explore the objectives of both CMOs and CEOs when negotiating a marketing budget. The study reveals that their joint objective is to finalize a marketing budget that includes provision for resources that are commensurate with the KPIs expected from the marketing function, i.e., a calibrated marketing budget (CMB). Based on this insight, I advance budgeting theory and propose CMB as a dimension of the marketing budget sought by some CMOs. I also distinguish the marketing budget calibration process as distinct from other organizational budgeting processes and techniques. In Essay 2, I identify six unique marketing budgeting signals that CMOs use to lower the CEO’s agency concerns, thereby increasing the likelihood of obtaining approval for a CMB. Recognizing that the efficacy of these signals can vary with repeated use, I determine which signals are more (less) effective when repeatedly used by a CMO. This understanding is critical for CMOs to determine how often to repeat a signal to maximize its effectiveness. Taken together, this dissertation provides a theoretical foundation for advancing research on the marketing budgeting processes within organizations, offering new insights into the approval of marketing budgets.